Prostate gland localization with fiducial markers (Annals of Medical Research, 2022)
Aim: Prostate gland inter-intra fraction organ motion cause uncertainties on both target organ definition and risky organ doses. The aim of this study is to determine axis shifts between gold markers and pelvic bony structures by using electronic portal images and factors which affects these shifts at prostate cancer patients who had gold marker implantation before radiotheraphy.Materials-methods: This study involved 31 patients with prostate cancer who had placement of gold markers into the prostate gland before radiotheraphy. In the course of treatment, electronic portal images were used for field control with guidance of gold markers every other day. Treatment fields determined by using bony structures and gold markers respectively. Lateral, longitudinal and vertical axis shifts (minimum, mean, maximum) between gold markers and pelvic bony structures were evaluated and the factors which attracted these shifts were examined.Results: We assessed a total of 1683 electronic portal images, and we determined axis shifts between gold markers and bony structures mean laterally minimum 0,3 (0-3)mm, mean 0,4 (0,5-3,2)mm, maximum 3,2 (1-6)mm; longitudinally minumum 0.5 (0- 4) mm, mean 2.4 (0.8-8.4) mm and maximum 6.1 (2-12) mm; vertically minumum 0.5 (0- 2) mm, mean 1.8 (0.4-4) mm and maximum 4.3 (1-7). The relation between maximum lateral axis shift values and using hormone-replacement theraphy; minimum vertical axis shift values and body mass index were statiscally significant (p=0.02, p=0,03 ).Conclusion:We established a statistically significant relation between lateral axis shift maximum values and using hormone-replacement theraphy; minimum vertical axis shift values and body mass index(p=0.02, p=0,03 ). Treatment margin must be determined carefully, especially in patients who have elevate body mass index and use hormone theraphy, if gold markers can not be used.
Keywords: Prostate cancer; radiotheraphy; fiducial markers